MINAT PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KABUPATEN LABUHANBATU UTARA - Dedi Sahputra Napitupulu; Mahariah; Annisa Okatafera; Dwi Yudha Lesmana; salwa, mutia; Siti Rabiatul Adawiyah (ISTIQRA: Jurnal Hasil Penelitian, 2023)
Interest is a desire that motivates students to take part in learning, interest is very influential on students' goals in the future, in line with this explanation, this research aims to measure the interest interests of Madrasah Tsanawiah students in PAI subjects, both from lessons Aqidah Akhlak, history of Islamic culture, Jurisprudence, and Al-Quran Hadith. This research uses quantitative methods. Data collection in this research used a survey method in ten Tsanawiya Madrasahs in the city of Medan with a sample size of 200 people and the data collection method used was Google form. Based on the data that has been collected, the conclusion in this research shows that students' interest in Islamic religious education subjects with the sub-subjects of Aqidah, Morals, Jurisprudence, Islamic Tarekh, and the history of Islamic culture, is very high because it can improve the character of people who are still too lay people of Islam. Apart from that, Islamic religious education subjects can guide and invite people to a better path, then every good action and behavior that is done will result in calm in the life of the world and the end. Creating a peaceful life is very easy, namely by doing good deeds and avoiding the prohibitions of Allah SWT contained in the Koran and Hadith.